2002
DOI: 10.1677/joe.0.1750261
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interleukin-1 beta activates the hypothalamic-pituitary-interrenal axis in rainbow trout, Oncorhynchus mykiss

Abstract: The present study provides the first direct evidence that implicates fish cytokines as the effector molecules by which the immune system signals the neuroendocrine system and activates the hypothalamic-pituitary-interrenal stress axis. I.p. injections of trout recombinant interleukin-1 (rIL-1 ) or E. coli lipopolysaccharide (LPS), at concentrations known to induce immune/inflammatory responses in vivo (0·1-0·6 nmol/kg and 1·3 mg/kg respectively), significantly elevated plasma cortisol levels in a dose-and/or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 29 publications
6
34
1
Order By: Relevance
“…When we injected seabream with 8 mg/kg i.p. of bacterial endotoxin to induce infection, it provoked a marked rise in plasma cortisol levels similar to those previously described (Balm et al 1995, Holland et al 2002 and to the results previously reported (Acerete et al 2007). This produced a cortisol peak after 6 h (threefold the controls) and a progressive decrease in cortisol until 72 h, which are similar to the results reported in rats (Grinevich et al 2001) where a single LPS injection stimulated plasma cortisol levels.…”
Section: Discussionsupporting
confidence: 90%
“…When we injected seabream with 8 mg/kg i.p. of bacterial endotoxin to induce infection, it provoked a marked rise in plasma cortisol levels similar to those previously described (Balm et al 1995, Holland et al 2002 and to the results previously reported (Acerete et al 2007). This produced a cortisol peak after 6 h (threefold the controls) and a progressive decrease in cortisol until 72 h, which are similar to the results reported in rats (Grinevich et al 2001) where a single LPS injection stimulated plasma cortisol levels.…”
Section: Discussionsupporting
confidence: 90%
“…ACTH secretion seems also to be some control of IL-6 as high IL-6 levels have shown correlated with higher ACTH and cortisol levels (Zarkovic et al 2008). In fish, several studies have shown a similar bi-directional communication between HPI-Axis and cytokines (Tort 2011). Holland et al (2002 showed that recombinant IL-1injection raises cortisol levels, and injection of lipopolysaccharide (LPS) raised plasma cortisol in yellow perch (Haukenes and Barton 2004) and promoted StAR HK expression in gilt-head bream (Castillo et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Administration of homologous interleukin (IL)-1 activates the hypothalamo-pituitary-interrenal axis in rainbow trout (Holland et al 2002). In man, ghrelin inhibits expression of IL-1 , IL-6, and tumor necrosis factor (TNF)-in T cells and monocytes, suggesting that ghrelin modulates cell-to-cell interaction in leukocytes during inflammatory processes (Dixit et al 2004).…”
mentioning
confidence: 99%